Managing the Systems Approach to Develop Efficient and Effective Virtual Learning Environments - Bajbouj, Khawla Ahmed (International Journal of Excellence in Smart Learning, 2024)
This research paper aims to discuss two different yet interrelated concepts: the systems approach (SA) and the virtual learning environment (VLE). This paper reflects on the importance of managing a virtual learning environment based on a new alternative modern SA in which technology is integrated within its components. It attempts to explain the impeded functions pertinent to managing the systematic application of the SA and VLE in real-world situations that may lead to an efficient virtual instructional environment (VIE). This scientific endeavor has confirmed the issues projected in the purpose of the study.